Straw bale gardens : the breakthrough method for growing vegetables anywhere, earlier, and with no weeding - Karsten, Joel, 1969- (Cool Springs Press, 2013)
Straw Bale Gardens teaches gardening in a way that isn't only new but is thoroughly innovative and revolutionary to home gardening. It solves every impediment today's home gardeners face: bad soil, weeds, a short growing season, watering problems, limited garden space, and even physical difficulty working at ground level. Developed and pioneered by author and garden expert Joel Karsten, straw bale gardens create their own growing medium and heat source so you can get an earlier start. It couldn't be simpler or more effective: all you need is a few bales of straw, some fertilizer, and some seeds or plants, and you can create a weedless vegetable garden anywhere--even in your driveway.